Utilization of E-Learning on Instruction in The Junior High School - I Gde Wawan Sudatha; I Nyoman Jampel; I Made Tegeh (International Conference on Technology and Educational Science)
E-learning is a type of teaching and learning that allows the delivery of teaching materials to students using internet, intranet or other computer network media. This research was aimed at describing 1) the use of e-learning for junior high school students in Singaraja City, and 2) the factors that support and inhibit learning with e-learning in junior high schools in Singaraja City. This research is descriptive research. Determination of research samples using stratified random sampling technique. School samples were used, namely: SMP Negeri 1 Singaraja, SMP Negeri 4 Singaraja, and SMP Lab. Undiksha. The results showed that: 1) that the level of application of learning with e-learning is very high, and 2) the factors that support learning with e-learning are (a) factors of facilities and infrastructures which include the existence of computer laboratories, multimedia room, ICT room, audio-visual media, as well as other facilities such as TVs, LCD projectors, and (b) human resource factors or teachers who have the enthusiasm to continue to improve competence while the factors that become obstacles in learning with e-learning are (a) busy teacher, (b) short time, and (c) lack of experts in the field of ICT.